Estudio de la prevalencia del nacimiento y de la presencia de bucle caudal extracraneano de arterias cerebelosas posteroinferiores (ACPI) en una población estudiada por angiografía cerebral.: https://doi.org/10.59156/revista.v36i04.581 - Morón, Félix; Leyes, Paula; Dorozuk, Gustavo; Ypa, Paula; Goland, Javier (Revista Argentina de Neurocirugía, 2023)
Objective: Determine the prevalence of the origin of the posterior inferior cerebellar artery at the extracranial level, the presence of the extracranial caudal loop and the relationships with adjacent bone structures, in a population studied by angiography of supra-aortic vessels.Material and methods: Prospective, descriptive study of a consecutive sample carried out for one year of all the patients who underwent catheterization of neck and brain vessels in a neurointervention service.The studies were carried out in two digital angiographs indistinctly in incidence profile, with and without image digitization, focused on the craniocervical junction in all patients between 18 and 80 years of age studied for one year. The place of origin of the PICA arteries and the presence of extracranial loops were observed by direct vision in the studies without and with subtraction. An extracranial loop was defined as the presence of a curved segment of the artery in a caudal direction that extends below the foramen magnum. Interobserver agreement was sought between 2 professionals independently.Result: Of the 404 procedures performed in the period studied, 288 patients entered the study, of which 152 were women. The average age was 49.2 years. 422 ACPI were analyzed, 214 right and 208 left. A total of 102 ACPI with extracranial loops were observed, representing 24.1% of the total: 49 right (48%) and 53 left (52%). In relation to arteries of extracranial origin, a total of 58 (13.7%) were observed, of which 29 were right (50%). In 10 cases, birth and extracranial loop were observed in the same artery (10%) and in two cases birth and bilateral extracranial loop (3.9%). In 13 cases the vertebral artery was terminal in ACPI, of which 5 presented an extracranial loop, representing 38.5% of its population, being entirely from the right territory.Conclusions: The prevalence of extracranial origin of ACPI in the population studied by angiography was 13.7% and the prevalence of extracranial loop was 24%. Both percentages are within the results found in previous anatomical and imaging studies: 0.7 to 20% and 9.5 to 35% respectively. The prevalence of extracranial loop in vertebral arteries ending in PICA was 38.5%, being significantly higher than the reported studies.
Keywords: PICA; Loop; Extracranial